Product properties for pairwise lindelof spaces. - Kilicman, Adem; Saleh, Zabidin (Cornell University Library, 2011)
In this paper we study finite product of pairwise Lindelof bitopological spaces. We show that the product properties for pairwise Lindelof spaces are not preserved. Further, we provide some necessary conditions for these spaces to be preserved under a finite product.